Kampanye Kandidat Presiden Amerika Serikat dalam Meraih Simpati Para Pemilih - Hirzi, Aziz Taufik (Mediator, 2008)
US presidential elections become one of the hottest issues in political world nowadays. It draws attention not only from local federal countries, but also attracts international audiences as the candidates from Democrats are challenging each other. From political communication studies, the campaign stages of US presidential elections reflected a mature democratic political system which stands on many humanity values, such as truth, honesty, fairness, and respect for others. The issue toward candidate’s cleanliness was predicted would be determiner for each candidate whether or not they will move further in electoral process. People, or potential voters will count on cleanliness more than any other else.